Mediating Effect of Work-Family Conflict on the Relationship Between Long Commuting Time and Workers' Anxiety and Insomnia - Seong-Uk Baek; Jin-Ha Yoon; Jong-Uk Won (Elsevier, 2023)
Background: Our study aimed to investigate the mediating role of work-family conflict (WFC) on the relationship between long commutes and workers' anxiety and insomnia. Methods: Our study measured the two dimensions of WFC, time-related, and strain-related, which were considered multiple mediators. The mediating effect of WFC on anxiety and insomnia was investigated by decomposing the total effect into a direct effect (long commuting time → anxiety or insomnia) and an indirect effect (long commuting time → WFC → anxiety or insomnia). The combined indirect effect (joint indirect effect) of strain-related WFC and time-related WFC was estimated. The effects were presented as odds ratios and 95% confidence intervals (CIs). Results: The direct effect of 120 min or longer of commuting time was 1.39 (95% CI: 1.17-1.65) times increase in the odds of anxiety and 1.64 (95% CI: 1.41-1.90) times increase in the odds of insomnia than those whose commuting time was less than 60 min. In the case of indirect effects, those whose commuting time was 120 min or longer had 1.13 times higher odds of anxiety (95% CI: 1.07-1.18) and 1.12 times higher odds of insomnia (95% CI: 1.07-1.17) via WFC. The joint indirect effects accounted for 26.4% and 18.5% of the total effect on anxiety and insomnia, respectively. The longer the commuting time, the stronger both direct and indirect effects. Conclusions: Our findings highlight the mediating effect of WFC on the relationship between long commuting times and workers' anxiety and insomnia.